Effects of resistance training on hypertrophy, strength and tensiomyography parameters of elbow flexors: role of eccentric phase duration - Kojić, Filip; Ranisavljev, Igor; Ćosić, Dušan; Popović, Dejana; Stojiljković, Stanimir; Ilić, Vladimir (Biology of Sport, 2021)
The aim of the study was to compare the effects of two different training protocols, which differ in the duration of the eccentric phase, on the one-repetition maximum (1RM), thickness and contractile properties of elbow flexors. Twenty untrained college students were randomly divided into two experimental groups, based on the training tempo: FEG (Faster Eccentric Group: 1/0/1/0) and SEG (Slower Eccentric Group: 4/0/1/0). Training intervention was a biceps bending exercise, conducted twice a week for 7 weeks. The intensity (60–70% RM), sets (3–4) and rest intervals (120 s) were held constant, while repetitions were performed until it was not possible to maintain a set duration. In the initial and final measurements, 1RM, muscle thickness and tensiomyography parameters – contraction time (Tc) and radial deformation (Dm) – were evaluated. An ANCOVA model (using baseline outcomes as covariates) was applied to determine between-group differences at post-test, while Pearson’s product-moment correlation coefficient was used to investigate the relationship between absolute changes in muscle thickness and Dm. Muscle strength increase was greater for SEG than for FEG (6.0 ± 1.76 vs. 3.30 ± 2.26 kg, p < 0.01). In both groups muscle thickness increased equally (FEG: 3.24 ± 2.01 vs. SEG: 3.57 ± 1.17 mm, p < 0.01), while an overall reduction in Dm was observed (FEG: 1.99 ± 1.20 vs. SEG: 2.26 ± 1.03 mm, p < 0.01). Values of Tc remained unchanged. A significant negative relationship was observed between changes in muscle thickness and Dm (r = -0.763, Adj.R² = 0.560, p < 0.01). These results indicate that the duration of the eccentric phase has no effect on muscle hypertrophy in untrained subjects, but that slower eccentric movement significantly increases 1RM.